2001
DOI: 10.1002/ajp.1034
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cognitive challenge on self‐directed behaviors by chimpanzees (Pan troglodytes)

Abstract: In primates, including humans, scratching and other self-directed behaviors (SDBs) have recently been reported to be differentially displayed as a function of social interactions, anxiety-related drugs, and response outcomes during learning tasks. Yet few studies have focused on the factors influencing SDBs in our closest living relatives, the chimpanzees (Pan troglodytes). Furthermore, no previous experimental study has examined handedness of SDBs as a function of changes in task difficulty. Using matching-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
75
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 38 publications
(54 reference statements)
3
75
1
Order By: Relevance
“…Indeed, scratching the left side of the body with the right hand was the most frequently observed response during the experimental condition. These results are largely consistent with the previous findings reported by Leavens et al (2001) in a much smaller cohort of chimpanzees and somewhat consistent with previous findings in wild chimpanzees (Marchant & McGrew, 1996;McGrew & Marchant, 2001). We believe the most parsimonious explanation for these findings is that mediation of arousal is controlled by the right hemisphere of chimpanzees.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Indeed, scratching the left side of the body with the right hand was the most frequently observed response during the experimental condition. These results are largely consistent with the previous findings reported by Leavens et al (2001) in a much smaller cohort of chimpanzees and somewhat consistent with previous findings in wild chimpanzees (Marchant & McGrew, 1996;McGrew & Marchant, 2001). We believe the most parsimonious explanation for these findings is that mediation of arousal is controlled by the right hemisphere of chimpanzees.…”
Section: Discussionsupporting
confidence: 93%
“…In previous studies in which stress was induced by increasing cognitive tasks demands, Leavens et al (2001) reported that eight chimpanzees scratched more with the right hand under more stressful conditions. In addition, scratching was directed significantly more to the left compared to the right side of the body.…”
mentioning
confidence: 96%
“…Further investigations are also required to explore handedness within a social or stressful context, as a rise in the proportion of left-handed actions within a social context may prove to be a useful indirect marker of cerebral lateralization for processing social-emotional content [e.g. 77] and increasing task complexity [64]. Finally, in order to verify the manipulative intent of the unimanual action, it would be beneficial to also explore the different aspects of the behaviors that occur once unimanual action makes contact with the target object (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…10,61,62]. Alternatively, it has been noted that orangutans a exhibited a significant left-hand preference for scratching and for fine manipulation of parts of the face in rehabilitated orangutans [63], while chimpanzees exhibited a significant increase in left-handed self-directed behaviors with increased in task complexity [64] contending that self-directed behaviors may be influenced by motivational factors underpinned by a right hemisphere dominance within both social and nonsocial contexts. Along with inconsistent finding across laboratories, some results, particularly related to chimpanzees, have been challenged on methodological grounds [e.g.…”
mentioning
confidence: 99%
“…Repeatability assesses the proportion of variation in behaviour that is due to inter-individual variation, as compared to intra-individual variation, and thus measures an individual's behavioural consistency. Second, I addressed the trait correlation structure to understand which social behavioural patterns are expressed as broader trait categories, and whether social behaviours form syndromes with non-social behaviours, including general activity and self-directed behaviours (SDB) that can be considered as indicators of anxiety (Leavens et al 2001;Maestripieri et al 1992;Schino et al 1996). I expected to find personality traits in the realms of grooming and aggression (Anestis 2005;Foster et al 2009;Uher et al 2008), but refrained from predictions concerning other potential personality traits or their structural organisation.…”
mentioning
confidence: 99%